Identifikasi local climate zone dan sebaran spasial land surface temperature di Kota Semarang tahun 2019 - Fitria Nucifera; Sola Tri Astuti (Universitas Negeri Yogyakarta, 2021)
Urbanization in Indonesia has continued to increase starting in 2011. The increasing population impacted the conversion of agricultural land to non-agricultural land. Reduction in the proportion of green open space results in changes in the spatial pattern of the area which affects the increase in urban temperatures, thus triggering the occurrence of UHI. This study aims to determine the spatial distribution of LST and LCZ in Semarang City by using quantitative descriptive analysis. Semarang City has LST variation values between 24.72ºC to 32.56ºC. Semarang City has 13 types of LCZ, consisting of 6 LCZs based on building types and 7 LCZs based on land cover. LCZ type B is the largest LCZ which reaches 58.52 km² or 15.12% of the total area. The highest LST is LCZ type E, reaching 32.10 °C which displays rock landscapes or asphalt cover. The lowest value is LCZ type G, reaching 25.09°C, which is an open water body such as reservoirs and ponds. Climate-based urban planning can be carried out in the LCZ area which has a high temperature by observing and mitigating it through the constituent components of each LCZ.